DICER1 Syndrome: A New Cancer Syndrome - Schultze-Florey, R. E.; Graf, N.; Vorwerk, P.; Koscielniak, E.; Schneider, D. T.; Kratz, C. P. (Klinische Pädiatrie, 2013)
Recently, germline mutations of DICER1 have been identified in patients with rare neoplasms suggesting the existence of a newly discovered cancer prone syndrome. Initially, DICER1 mutations were identified in patients with familial pleuropulmonary blastoma. Subsequently, additional manifestations of the syndrome have been identified including cystic nephroma, medulloepithelioma, Sertoli-Leydig cell tumor and others. The DICER1 gene encodes an enzyme that is involved in the biogenesis of microRNAs. The entire tumor spectrum and the respective tumor risks are unknown. We are in the process of launching a natural history study aimed at identifying more information on this new cancer syndrome.
Keywords: DICER1 syndrome; pleuropulmonary blastoma; natural history study; cancer syndrome; altered miRNA biogenesis; Dicer1